Uncultivated Viral Populations Dominate Estuarine Viromes on the Spatiotemporal Scale - Mengqi Sun (American Society for Microbiology, 2021)
ABSTRACT Viruses are ubiquitous and abundant in the oceans, and viral metagenomes (viromes) have been investigated extensively via several large-scale ocean sequencing projects. However, there have not been any systematic viromic studies in estuaries. Here, we investigated the viromes of the Delaware Bay and Chesapeake Bay, two Mid-Atlantic estuaries. Deep sequencing generated a total of 48,190 assembled viral sequences (>5 kb) and 26,487 viral populations (9,204 virus clusters and 17,845 singletons), including 319 circular viral contigs between 7.5 kb and 161.8 kb. Unknown viruses represented the vast majority of the dominant populations, while the composition of known viruses, such as pelagiphage and cyanophage, appeared to be relatively consistent across a wide range of salinity gradients and in different seasons. A difference between estuarine and ocean viromes was reflected by the proportions of Myoviridae, Podoviridae, Siphoviridae, Phycodnaviridae, and a few well-studied virus representatives. The difference in viral community between the Delaware Bay and Chesapeake Bay is significantly more pronounced than the difference caused by temperature or salinity, indicating strong local profiles caused by the unique ecology of each estuary. Interestingly, a viral contig similar to phages infecting Acinetobacter baumannii (“Iraqibacter”) was found to be highly abundant in the Delaware Bay but not in the Chesapeake Bay, the source of which is yet to be identified. Highly abundant viruses in both estuaries have close hits to viral sequences derived from the marine single-cell genomes or long-read single-molecule sequencing, suggesting that important viruses are still waiting to be discovered in the estuarine environment. IMPORTANCE This is the first systematic study about spatial and temporal variation of virioplankton communities in estuaries using deep metagenomics sequencing. It is among the highest-quality viromic data sets to date, showing remarkably consistent sequencing depth and quality across samples. Our results indicate that there exists a large pool of abundant and diverse viruses in estuaries that have not yet been cultivated, their genomes only available thanks to single-cell genomics or single-molecule sequencing, demonstrating the importance of these methods for viral discovery. The spatiotemporal pattern of these abundant uncultivated viruses is more variable than that of cultured viruses. Despite strong environmental gradients, season and location had surprisingly little impact on the viral community within an estuary, but we saw a significant distinction between the two estuaries and also between estuarine and open ocean viromes.